Decolonizing democracy from Western cognitive imperialism - Mentan, Tatah, 1948- (Langaa Research & Publishing CIG, 2015)
There seems to be a sort of prevalent attitude in the Western world that its brand of democracy is something of a catch all solution for all the world's political problems. Hence, Western imperialism has always been sold under the pretext of spreading freedom and democracy. Democracy is beautiful. But it is no proof against imperialism. Whether democracy is causal is another whole consideration. It may be a case of the 'least bad of evil alternatives.' It may be a case of a state of social and political development over and above the way people organize themselves. It may be the fate of rational life on a planet with insufficient energy reserves to support locomotion without predation. But what gives anyone the right to go into a sovereign country and change its foundation through War? The whole democracy & freedom line is a lie to give Western imperialism a friendly face. Imperialism and its lie of spreading democracy is an unmitigated evil, whether for material gain, or the pride fostered by active participation in the machinery of state. Therefore, a people seeking to control their destiny must decolonize imposed Western democracy.